2007
DOI: 10.1038/nrc2130
|View full text |Cite
|
Sign up to set email alerts
|

The Delta paradox: DLL4 blockade leads to more tumour vessels but less tumour growth

Abstract: Anti-angiogenesis therapies have emerged as important treatment options for several types of tumours. To date, these therapies have focused on blocking the vascular endothelial growth factor (VEGF) pathway. A recent series of papers have shown that one ligand for the Notch receptors, Delta-like ligand 4 (DLL4), is normally induced by VEGF and is a negative-feedback regulator that restrains vascular sprouting and branching. Consistent with this role, the deletion or inhibition of DLL4 results in excessive, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
203
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(215 citation statements)
references
References 42 publications
8
203
0
4
Order By: Relevance
“…Additionally, Notch and Notch ligands, for example, Delta-like 4 (Dll4), are robustly expressed in tumor endothelial cells in comparison with that in neighboring, normal tissue vessels (Mailhos et al, 2001), and vascular endothelial growth factor, which can be predominately produced by tumor cells, can induce endothelial cells to express Notch1 and Dll4 (Liu et al, 2003;Noguera-Troise et al, 2006;Ridgway et al, 2006). In fact, blockade of Dll4-Notch signaling is an emerging therapeutic approach to inhibit tumor angiogenesis (Thurston et al, 2007;Dufraine et al, 2008;Yin et al, 2010). It appears that both the status of Notch signaling and outcomes of Notch pathway activation in terms of cellular behavior are opposite in melanoma and Fbs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Notch and Notch ligands, for example, Delta-like 4 (Dll4), are robustly expressed in tumor endothelial cells in comparison with that in neighboring, normal tissue vessels (Mailhos et al, 2001), and vascular endothelial growth factor, which can be predominately produced by tumor cells, can induce endothelial cells to express Notch1 and Dll4 (Liu et al, 2003;Noguera-Troise et al, 2006;Ridgway et al, 2006). In fact, blockade of Dll4-Notch signaling is an emerging therapeutic approach to inhibit tumor angiogenesis (Thurston et al, 2007;Dufraine et al, 2008;Yin et al, 2010). It appears that both the status of Notch signaling and outcomes of Notch pathway activation in terms of cellular behavior are opposite in melanoma and Fbs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the extension/formation of the new vasculature has been a recent subject of intense interest and has led to development of VEGF inhibitors for antiangiogenic tumor therapies. Recent studies have also unveiled the pivotal importance of Notch signaling in the process of angiogenesis, with specific focus on 2 Notch ligands DLL4 and JAG1 (5,(38)(39)(40)(41)(42). It is suggested that branching of new vasculature is a result of modulation of Notch signaling within the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This process is a result of endothelial cell proliferation, migration, and differentiation along the VEGF gradient produced by the tumor (1). In addition to VEGF regulation of vascular development, branching and expansion of the vasculature are under the control of cell-cell activation of Notch signaling (5). Notch signaling is activated by membrane-bound ligand presentation to a Notch receptor on adjacent cells.…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1α activates genes related to angiogenic factors, glycolytic enzymes and glucose transporters [32][33][34]. It has been reported that VEGF, which is a target gene for HIF signaling increases expression of DLL4, which is a ligand of Notch pathway, and, in turn, up-regulates Notch expression, leading to productive Notch signaling [35][36][37]. Moreover, Snail and Slug, which induced epithelial mesenchymal transition (EMT), were reported to be involved by the interaction of Notch and HIF under hypoxia (29.…”
Section: Discussionmentioning
confidence: 99%